2017
DOI: 10.1253/circj.cj-17-0197
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Status in Patients With Chronic Thromboembolic Pulmonary Hypertension

Abstract: Background: The present comparative study with healthy volunteers was conducted to investigate the depressive status and temperament in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Methods and Results:The results of the temperament and personality scale test, and the Quick Inventory of Depressive Symptomatology-Self Report revealed that CTEPH patients have a significantly higher depressive status than healthy volunteers.Conclusions: It may be that CTEPH patients are more likely to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…For example, Suzuki et al reported that 7% of their patients with CTEPH had a diagnosis of schizophrenia, 20 as did 3.9% of our patients; both these figures are higher than the prevalence of schizophrenia in the general population 21 . Furthermore, Funabashi et al reported a higher frequency of depression in patients with CTEPH 22 . Our group has recently identified that a Jamieson classification of III or IV and a high PVR were associated with poor survival, although similar survival rates were recently observed in patients with CTEPH treated by BPA, PEA, and medication between 2009 and 2016 23 .…”
Section: Discussionsupporting
confidence: 41%
“…For example, Suzuki et al reported that 7% of their patients with CTEPH had a diagnosis of schizophrenia, 20 as did 3.9% of our patients; both these figures are higher than the prevalence of schizophrenia in the general population 21 . Furthermore, Funabashi et al reported a higher frequency of depression in patients with CTEPH 22 . Our group has recently identified that a Jamieson classification of III or IV and a high PVR were associated with poor survival, although similar survival rates were recently observed in patients with CTEPH treated by BPA, PEA, and medication between 2009 and 2016 23 .…”
Section: Discussionsupporting
confidence: 41%
“…Other factors being possibly associated with worse quality of life include higher clot burden at index PE event, abnormal NT-proBNP at index PE event, persistent right ventricular dysfunction, as well as non-VTE comorbidities such as COPD obesity and cancer (8,55,59,(63)(64)(65)(66)(67)(68)(69)(70). As it may be expected, the association between CTEPH and poor quality of life has been unequivocally established (71)(72)(73)(74).…”
Section: Impact Of Cteph and The Post-pe Syndromementioning
confidence: 97%
“…16 Funabashi et al reported that 37.5% of CTEPH patients in their study had depression and that CTEPH patients were significantly more depressed than healthy individuals (37.5% vs 8.9%). 17 A study conducted by Pfeuffer et al compared PAH and CTEPH patients, reporting that the rate of depression was higher among those with CTEPH than those with PAH (56% vs 30%; p=0.03). 18 We found only one mixed-method study on PH patients and their symptom distress: in a study conducted by Muntingh et al of 67 PAH patients, participants reported low and fluctuating energy levels, difficulty with loss of abilities, worries about the future, restricted ability to fulfil their roles, and being misunderstood by others.…”
Section: Open Accessmentioning
confidence: 99%
“…This finding was similar to the findings of prior research. [12][13][14][15][16][17][18] This suggests, that despite dramatic advances in treatment methods that have improved life expectancy, mental health has not improved. To better understand these results, we conducted qualitative interviews with participants who had depressive symptoms.…”
Section: Integration Of the Quantitative And Qualitative Datamentioning
confidence: 99%
See 1 more Smart Citation